Rituximab for the Treatment of Relapses in ANCA-associated Vasculitis - Miloslavsky, EM (Arthritis Rheumatol, 2014)
INTRODUCTION: Disease relapses are frequent in antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV). We evaluated the outcomes of patients re-treated with rituximab (RTX) and prednisone for severe disease relapses. METHODS: The Rituximab in AAV trial was a randomized, double-blind, placebo-controlled trial comparing the rates of remission induction among patients treated with RTX (n = 99) and patients treated with cyclophosphamide (CYC) followed by azathioprine (AZA) (n = 98). Prednisone was tapered to discontinuation after 5.5 months. After achieving remission, patients who experienced a severe disease relapse between months 6 and 18 were eligible to receive RTX and prednisone on an open-label basis according to a pre-specified protocol. Investigators remained blinded to the original treatment assignment. RESULTS: Twenty-six patients received treatment with RTX for disease relapse after initially achieving remission on their originally assigned treatment. Fifteen patients were initially randomized to RTX and 11 to CYC/AZA. Thirteen (87%) of the patients originally assigned to RTX and 10 (91%) originally assigned to CYC/AZA achieved remission again with open-label RTX, an overall percentage of 88%. Half of the patients treated with open-label RTX were able to discontinue prednisone entirely. Patients in this cohort experienced fewer adverse events compared to the overall study population (4.7 adverse events/patient-year versus 11.8 adverse events/patient-year, respectively). CONCLUSION: Re-treatment of AAV relapses with RTX and glucocorticoids appears to be a safe and effective strategy, regardless of previous treatment.